Implementation of Orderly Administration in the Bookkeeping and Documentation System of Dasawisma Anggur Merah 3 RT 08 in Bukit Timah Subdistrict - Dila Erlianti; Lilis Wahyuni; Wagimin Wagimin; Sobirin Sobirin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This Community Service Program (PkM) was motivated by the low quality of administrative order in the bookkeeping and document management system of Dasawisma Anggur Merah 3 RT 08, Bukit Timah Village, characterized by unsystematic data recording, weak documentation practices, and limited understanding of accountable and organized administration. The objective of this program was to strengthen the capacity of Dasawisma in implementing orderly administration through the development of structured, transparent, and sustainable bookkeeping and documentation systems. The method applied was a participatory community organizing approach, implemented through socialization, technical assistance, simple bookkeeping training, hands-on documentation practices, and participatory evaluation. The results indicate a significant improvement in the understanding of Dasawisma members regarding the importance of administrative order, behavioral changes in record-keeping and document management, the establishment of a more structured bookkeeping system, and the emergence of collective awareness of administration as a foundation for program planning and decision-making. In addition, local leaders (local leaders) emerged as driving forces in strengthening administrative management and institutional capacity. This program contributes to the creation of more professional, accountable, and sustainable governance of Dasawisma organizations in community-based empowerment initiatives.